Kasus Penistaan Agama pada Berbagai Era dan Media di Indonesia - Yaya Mulya Mantri (Definisi: Jurnal Agama dan Sosial Humaniora, 2022)
Religion Blasphemy cases occur in various media based on the era. Cases of blasphemy in the media initially occurred through print media intermediaries, which began during the Dutch colonial era and the New Order. As technology advances, internet media beats print and electronic media. Cases of blasphemy that initially occurred in the media, then mushroomed in the internet media. This article examines four cases of blasphemy that occurred in four different eras. First, the case of Djawi Hiswara, which occurred during the Dutch colonial era, the second case of Arswendo, which occurred during the New Order era, the third case of Ahok, which occurred in the post-reform era, and the fourth Kece cases that occurred during the Covid-19 pandemic. The method used is comparative-descriptive by comparing the four cases and then analyzing them based on tolerance indicators. There are four indicators of tolerance, namely (1) is goal, (2) tolerance is open and receptive to the beauty of difference, (3) tolerance is respect for individuals and differences, and (4) the seed of tolerance is love while the seed of intolerance is indifference. The cases that meet the first indicator are the Djawi Hiswara case and the Ahok case, while the Arswendo case and the Kece case do not meet the first indicator. The four cases did not meet the second, third, and fourth indicators.